The Mutational Landscape of the Oncogenic MZF1 SCAN Domain in Cancer - Nygaard, Mads; Terkelsen, Thilde; Vidas Olsen, André; Sora, Valentina; Salamanca Viloria, Juan; Rizza, Fabio; Bergstrand-Poulsen, Sanne; Di Marco, Miriam; Vistesen, Mette; Tiberti, Matteo; Lambrughi, Matteo; Jäättelä, Marja; et al. (Frontiers in Molecular Biosciences, 2016)
SCAN domains in zinc-finger transcription factors are crucial mediators of protein-protein interactions. Up to 240 SCAN-domain encoding genes have been identified throughout the human genome. These include cancer-related genes, such as the myeloid zinc finger 1 (MZF1), an oncogenic transcription factor involved in the progression of many solid cancers. The mechanisms by which SCAN homo- and heterodimers assemble and how they alter the transcriptional activity of zinc-finger transcription factors in cancer and other diseases remain to be investigated. Here, we provide the first description of the conformational ensemble of the MZF1 SCAN domain cross-validated against NMR experimental data, which are probes of structure and dynamics on different timescales. We investigated the protein-protein interaction network of MZF1 and how it is perturbed in different cancer types by the analyses of high-throughput proteomics and RNASeq data. Collectively, we integrated many computational approaches, ranging from simple empirical energy functions to all-atom microsecond molecular dynamics simulations and network analyses to unravel the effects of cancer-related substitutions in relation to MZF1 structure and interactions.